A Scoping Review of the Relationships Between Quality Assurance, Accreditation and Program Evaluation in Higher Education - Findlay, Shannon (Université d'Ottawa / University of Ottawa, 2024)
Quality assurance is a term used broadly across many professions and what it encompasses varies. This scoping review studies what is known of the relationships between quality assurance (QA), program evaluation, and accreditation in the higher education literature and what gaps exist that could benefit from additional research. The results of this study suggest that accreditation can be part of QA processes, as can program evaluation, but there is a paucity of research that explicitly addresses the relationships between the three concepts. More research is required to describe the relationships between the concepts, and it is suggested that this be done relative to professions.
Keywords: program evaluation; accreditation; quality assurance; higher education